Analysis Of Price, Customer Experience, And E-Word Of Mouth On Customer Loyalty Of Shopee Users - Nihusnasari, Sabela Ayu; Prasojo, Aji (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This study aims to examine the influence of price, customer experience, and e-WOM on customer loyalty among Shopee users. Using a quantitative approach with a causal research design, the population includes Management students at UN PGRI Kediri, class of 2021. A total of 183 respondents were selected through simple random sampling. Data were collected using a five-point Likert scale questionnaire distributed online via Google Form, with instruments tested for validity and reliability. Data analysis involved classical assumption testing, multiple linear regression, Adjusted R², and hypothesis testing using SPSS version 25. Results show that price, customer experience, and e-WOM significantly influence customer loyalty, both partially and simultaneously. Customer experience emerged as the most dominant factor. The study suggests that Shopee should focus on enhancing customer experience and digital engagement to strengthen user loyalty